Histopathological spectrum of neoplastic lesions of female reproductive system-a two-year experience in Eastern Nepal - Singh, Mrinalini; Jha, Krishna Kumar; Poudyal, Prija; Kafle, Santosh Upadhyay (International Journal of Research in Medical Sciences, 2018)
Background: Neoplastic lesions of female reproductive system (FRS) consist majority of surgical cases. The aim of this study is to find out the frequency distribution of tumors occurring in FRS. Methods: This is a retrospective study carried out in Birat Medical College, situated in eastern Nepal. All formalin fixed surgical specimen of FRS from August 2015 to September 2017 were subjected for histopathology and examined under light microscopy. All neoplastic lesions were included, and non-neoplastic lesions were excluded from the study. Results: A total number of ninety (90) histopathological tissues representating various types of neoplastic lesion of FRS were studied. Out of which 6 (6.6%) tumors were from uterine cervix, (including 1 cervical leiomyoma and 5 squamous cell carcinoma cervix) 45(50%) tumors were from uterine body, (all leiomyoma) 20 (22.2%) tumors were from ovary (including 9 mature teratoma, 1 immature teratoma, 6 mucinous cystadenoma and 4 cases of serous cystadenoma) and 19 (21.2%) tumors were from breast (including 16 fibroadenoma, 1 lactational adenoma, 2 infiltrating ductal carcinoma and 1 comedo carcinoma). Majority 81(90%) were benign and 9 (10%) were malignant. Most common benign tumor was leiomyoma of uterine body and most common malignant tumor was squamous cell carcinoma of uterine cervix both commonly occurring in the age group of 41-50 years. Conclusions: Benign tumor, leiomyoma is the common tumor occurring in FRS. Carcinoma of the cervix is the common malignant tumor.